Simulation of Rayleigh Bernard convection using lattice Boltzmann method - Muhammad Aiman, Abdul Moin (2009)
In this thesis, a method of lattice Boltzmann is introduced. Lattice Boltzmann Method is to build a bridge between the microscopic and macroscopic dynamics, rather than to deal with macroscopic dynamics directly. In other words, LBM is to derive macroscopic equations from microscopic dynamics by means of statistic, rather than to solve macroscopic equations. Then, the methodology and general concepts of the lattice Boltzmann method are introduced. Next, a thermal lattice Boltzmann model is developed to simulate incompressible thermal flow. This report describes the flow pattern of Rayleigh Bernard Convection. This project will be focusing at low Rayleigh number and discretization of microscopic velocity using 9-discrete velocity model (D2Q9) and 4-discrete velocity model (D2Q4). This two discrete velocity model is applying the Gauss-Hermitte quadrate procedure. Rayleigh Bernard Convection and Lattice Boltzmann Method have been found to be an efficient and numerical approach to solve the natural convection heat transfer problem. Good Rayleigh Bernard Convection flow pattern agreement was obtained with benchmark (previous study).